Protective Effects and Mechanisms of Luteolin against Acute Respiratory Distress Syndrome: Network Pharmacology and In vivo and In vitro Studies - Li, Quan; Chen, Juan; Ren, Yi; Yang, Zhizhou; Wang, Mengmeng; Zhang, Wei; Cao, Liping; Sun, Haijun; Nie, Shinan; Sun, Zhaorui (Current Pharmaceutical Design, 2024)
Background: Acute Respiratory Distress Syndrome (ARDS) is an acute life-threatening disease, and luteolin has the potential to become a therapeutic agent for ARDS. However, its mechanism of action has not yet been clarified. Objective: The present study explored the potential effects and mechanisms of luteolin in the treatment of ARDS through network pharmacology analysis and verified them through biological experiments. Methods: The potential targets of luteolin and ARDS were obtained from online databases. Functional enrichment and protein-protein interaction (PPI) analyses were performed to explore the underlying molecular mechanisms and to identify hub targets. Molecular docking was used to verify the relationship between luteolin and target proteins. Finally, the effects of luteolin on key signaling pathways and biological processes were verified by in vitro and in vivo experiments. Results: A total of 146 luteolin- and 496 ARDS-related targets were extracted from public databases. The network pharmacological analysis suggested that luteolin could inhibit ARDS through the following potential therapeutic targets: AKT1, RELA, and NFKBIA. Inflammatory and oxidative stress responses were the main biological processes involved, with the AKT/NF-ΚB signaling pathway being the key signaling pathway targeted by luteolin for the treatment of ARDS. Molecular docking analysis indicated that luteolin had a good binding affinity to AKT1, RELA, and NFKBIA. The in vitro and in vivo experiments revealed that luteolin could regulate the inflammatory response and oxidative stress in the treatment of ARDS by inhibiting the AKT/NF- ΚB signaling pathway. Conclusion: Luteolin could reduce the production of reactive oxygen species and inflammatory factors by inhibiting the AKT/NF-ΚB signaling pathway, thus reducing apoptosis and attenuating ARDS.
Keywords: Luteolin